Trifluoperazine Enhances Accumulation and Inhibits Phosphohydrolysis of Phosphatidate in Thrombin-Stimulated Platelets - Holmsen, Holm; Dangelmaier, Carol A (Thrombosis and Haemostasis, 1990)
Trifluoperazine (TFP) in concentrations up to 10-15 μM increased the formation of phosphatidic acid (PA) in platelets treated with 0.5 U/ml of thrombin, while higher concentrations of TFP inhibited formation of PA. Liberation of arachidonate (AA) from platelet phospholipids was progressively inhibited as the concentration of TFP increased. At thrombin doses lower than 0.1 U/ml TFP, (≤25 μM) enhanced PA formation with either no effect on AA liberation (6 donors) or with much greater enhancement of PA formation than the decrease in liberation of AA (3 donors). The enhancement of PA formation by TFP did therefore not seem to be due to inhibition of phospholipase A2 (PLA2) by the phenothiazine, which has been suggested. We show further that TFP inhibits PA phosphohydrolase in platelet lysates, although with complex kinetics. It is therefore concluded that the enhancement of thrombin-induced PA production by TFP is not caused by inhibition of PLA2 but could be due to TFP-induced inhibition of PA phosphohydrolase.